American ginseng suppresses Western diet-promoted tumorigenesis in model of inflammation-associated colon cancer: role of EGFR - Dougherty Urszula; Mustafi Reba; Wang Yunwei; Musch Mark W; Wang Chong-Zhi; Konda Vani J; Kulkarni Anirudh; Hart John; Dawson Glyn; Kim Karen E; Yuan Chun-Su; Chang Eugene B; et al. (BMC, 2011)
Abstract Background Western diets increase colon cancer risk. Epidemiological evidence and experimental studies suggest that ginseng can inhibit colon cancer development. In this study we asked if ginseng could inhibit Western diet (20% fat) promoted colonic tumorigenesis and if compound K, a microbial metabolite of ginseng could suppress colon cancer xenograft growth. Methods Mice were initiated with azoxymethane (AOM) and, two weeks later fed a Western diet (WD, 20% fat) alone, or WD supplemented with 250-ppm ginseng. After 1 wk, mice received 2.5% dextran sulfate sodium (DSS) for 5 days and were sacrificed 12 wks after AOM. Tumors were harvested and cell proliferation measured by Ki67 staining and apoptosis by TUNEL assay. Levels of EGF-related signaling molecules and apoptosis regulators were determined by Western blotting. Anti-tumor effects of intraperitoneal compound K were examined using a tumor xenograft model and compound K absorption measured following oral ginseng gavage by UPLC-mass spectrometry. Effects of dietary ginseng on microbial diversity were measured by analysis of bacterial 16S rRNA. Results Ginseng significantly inhibited colonic inflammation and tumorigenesis and concomitantly reduced proliferation and increased apoptosis. The EGFR cascade was up-regulated in colonic tumors and ginseng significantly reduced EGFR and ErbB2 activation and Cox-2 expression. Dietary ginseng altered colonic microbial diversity, and bacterial suppression with metronidazole reduced serum compound K following ginseng gavage. Furthermore, compound K significantly inhibited tumor xenograft growth. Conclusions Ginseng inhibited colonic inflammation and tumorigenesis promoted by Western diet. We speculate that the ginseng metabolite compound K contributes to the chemopreventive effects of this agent in colonic tumorigenesis.